A new migration model based on the evaluation of processes load and lifetime on heterogeneous computing environments - Mello, R. F. de; Senger, L. J. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2004: Anais do XVI Symposium on Computer Architecture and High Performance Computing, 2004)
This paper presents a new model for evaluation of the positive and negative impacts related to the process migration on environments composed by heterogeneous capacity computers. On this model, a busy computer analyzes the occupation of each process and selects the more adequate for migration. The analysis and selection are done through a migration factor. This factor reflects how much the busy computer will be freed and how much the destination computer will be overloaded, in view of the migration of each process. The migrated processes are the ones that present migration factors to enhance the environment load balancing. The results from the carried out experiments have proved this model contributions when compared to related work. The contribution is the decrease in process average response time, which means higher performance.